2018
DOI: 10.1113/ep086641
|View full text |Cite
|
Sign up to set email alerts
|

Daily inspiratory muscle training lowers blood pressure and vascular resistance in healthy men and women

Abstract: Previous work has shown that inspiratory muscle training (IMT) lowers blood pressure after a mere 6 weeks, identifying IMT as a potential therapeutic intervention to prevent or treat hypertension. Here, we explore the effects of IMT on respiratory muscle strength and select cardiovascular parameters in recreationally active men and women. Subjects were randomly assigned to IMT (n = 12, 75% maximal inspiratory pressure) or sham training (n = 13, 15% maximal inspiratory pressure) groups and underwent a 6-week in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 76 publications
4
37
3
Order By: Relevance
“…It is worth noting that at REST the MIP60 training was able to evoke a significant bradycardia in presence of an unvaried SAP. This finding is in contrast with some studies suggesting that IMT of moderate intensity could lower arterial pressure while leaving unmodified HP values in both normotensive (Vranish and Bailey, 2015;DeLucia et al, 2018) and hypertensive (Ferreira et al, 2013) subjects. Even the improvement of arterial pressure regulation, reported in subjects with orthostatic hypotension such as those after spinal cord injury (Aslan et al, 2016), it is not evident in our study given that the baroreflex control is not affected by IMT.…”
Section: Limitations Of the Study And Future Developmentscontrasting
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that at REST the MIP60 training was able to evoke a significant bradycardia in presence of an unvaried SAP. This finding is in contrast with some studies suggesting that IMT of moderate intensity could lower arterial pressure while leaving unmodified HP values in both normotensive (Vranish and Bailey, 2015;DeLucia et al, 2018) and hypertensive (Ferreira et al, 2013) subjects. Even the improvement of arterial pressure regulation, reported in subjects with orthostatic hypotension such as those after spinal cord injury (Aslan et al, 2016), it is not evident in our study given that the baroreflex control is not affected by IMT.…”
Section: Limitations Of the Study And Future Developmentscontrasting
confidence: 99%
“…Conversely, no PRE-POST variation of BRS was observed and the usual trend of baroreflex markers with STAND was detected after MIP60 training. The lack of influences on the baroreflex regulation is in agreement with data derived during a session of breathing through an inspiratory resistance of small value (Convertino et al, 2004a) and with the long-term effects of an IMT training of moderate intensity (DeLucia et al, 2018). We suggest that the post-training changes of CRCS detected by TE RM→HP|SAP during STAND in MIP60 group are due to mechanisms unrelated to baroreflex.…”
Section: Effect Of the Orthostatic Challenge On Crcs In Post Conditionsupporting
confidence: 89%
“…One possibility is the use of respiratory muscle training (RMT) (Illi et al, 2012), in which intensive respiratory maneuvers are performed while no activity is required from the upper or lower limbs. Large decreases in systolic (SBP) and diastolic (DBP) blood pressure in normotensive adults were found after 6-weeks of strength-like RMT, but only when large pressures were used (Vranish and Bailey, 2015;DeLucia et al, 2018), a finding which has not been supported by others (Witt et al, 2007), including in more frail populations (Chiappa et al, 2008). Much less is known about potential changes on arterial stiffness brought by RMT, with a single investigation suggesting increased arterial compliance following RMT, without measuring PWV (DeLucia et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Large decreases in systolic (SBP) and diastolic (DBP) blood pressure in normotensive adults were found after 6-weeks of strength-like RMT, but only when large pressures were used (Vranish and Bailey, 2015;DeLucia et al, 2018), a finding which has not been supported by others (Witt et al, 2007), including in more frail populations (Chiappa et al, 2008). Much less is known about potential changes on arterial stiffness brought by RMT, with a single investigation suggesting increased arterial compliance following RMT, without measuring PWV (DeLucia et al, 2018). This is a topic that needs further clarification, as for example endurance and resistance training have been shown to decrease and increase arterial stiffness respectively (Collier et al, 2008), the latter possibly due to the pressure swings resulting from Valsalva maneuvers during intense muscle contractions (Heffernan et al, 2007b).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding endothelial function, several studies have demonstrated the effectiveness of yoga (Hunter et al, 2017 , 2018 ). However, the impact of slow breathing on endothelial and vascular function has not yet been demonstrated (Limberg et al, 2013 ; DeLucia et al, 2018 ). Multiple components of yoga such as physical poses ( asanas ), respiratory exercises ( pranayamas ), meditation, and devotional and lifestyle aspects have never been analyzed separately in order to assess specific benefits (Hartley et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%